Dengue fever: a re-emerging disease - Minhas, Sukhmeet; Pardal, Maninder Pal Singh (International Journal Of Community Medicine And Public Health, 2020)
Background: Dengue is a rapidly spreading mosquito borne disease. Dengue is now endemic in 100 countries worldwide. Methods: Cross sectional descriptive study design was used by the workers. We The workers obtained detailed information from each reported case. Active case finding by surveys during the period of the outbreak, besides a detailed environmental survey was also carried out. Standard statistical tools like calculating relative risk and Chi square were utilised for data analysis. Results: In all 17 cases who fulfilled the case definition criteria were admitted in the month of September 2019. Out of these 16 (94.11%) were confirmed by NS 1 Antigen ELISA, while 01 (05.88%) was probable case. The first case reported on 08 Sep 2019, followed by a sudden spurt in the number of cases. The weekly epidemic curve is depicted in (Figure 1). There were no complications or fatalities. Detailed environmental assessment of the area revealed Aedes mosquito breeding in artificial containers of water. The house index of 7.06%, while the container index was 6.06%. Conclusions: The above study thus highlights the necessity of strict environmental monitoring by all authorities concerned in the country to prevent morbidity and mortality due to Dengue fever and other mosquito borne diseases. The menace of Dengue fever will continue till we learn to manage our solid waste properly, as Dengue is after all a man-made disease due to improper solid waste disposal.